Identifikasi struktur sesar daerah manifestasi panas bumi “X” di Kabupaten Manggarai Nusa Tenggara Timur berdasarkan analisis Horizontal Gradient - Anik Fitrochaton Chasanah; Agus Setyawan; Dadan Dani Wardhana (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2018)
Area “X” located in Manggarai of East Nusa Tenggara is volcanic area in Indonesia which has the potential for geothermal to be indicated by the appearance of a geothermal manifestation of hot springs and fumarole or sulfatar. Processing data by analysis gradient horizontal has been done to determine the structure of fault. From the map complete Bouguer anomali (ABL) shows anomalies in the middle of the study area which is a crater form of Mount Poco Ranakah, Poco Manggung, Poco Mandasawu and Poco Kasteno. In the southwest of the study area there is a low anomaly associated with alteration zone of rocks and hot springs. The high anomaly to the North of the study area lies in the crumpled hills, so that the area is dominated by high anomaly values. Gradient analysis were performed determine the limits of lithogy and the structure of fault associated with the appearance of hot springs and fumarol or sulfate in the study area. Geothermal manifestastios MAP 6, MAP 7, MAP 8, F/S 1 and F/S 2 controlled by strike slip fault of horizontal gradient. Geothermal manifestations of MAP 1, MAP 4 and MAP 11 are located on geological fault trending Northeast-Southwest and Northwest-Southeast. Keywords: gravity data, gradient analysis